STRATEGIC COMMUNICATION AND MARKETING OF TEDO COFFEE SHOP IN ATTRACTING CUSTOMERS - Rachman Julian, Maulady; Kurniawan, Gogi (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2025)
This study analyzes the communication and marketing strategies implemented by Tedo Coffee Shop in attracting customer interest amidst the intense coffee shop competition in Sampang. The purpose is to describe and analyze how Tedo Coffee Shop designs and applies its communication and marketing strat-egies, and how both synergistically contribute to building customer interest.Using a qualitative descrip-tive approach, data were collected through in-depth interviews with the owner, manager, and several baristas, direct observation of communication and marketing activities at the café and on digital plat-forms, as well as analysis of relevant internal documentation. The unit of analysis is Tedo Coffee Shop as a business entity.The findings reveal that Tedo Coffee Shop utilizes an active social media strategy, par-ticularly on Instagram, to build brand awareness and create an appealing image among young custom-ers. Communication is also strengthened through direct, personal interactions between baristas and cus-tomers. Meanwhile, the marketing strategy focuses on offering unique coffee and non-coffee products, competitive pricing, and creating a cozy, Instagrammable café atmosphere to encourage positive custom-er experiences. The combination of strong visual communication and attractive marketing offerings has proven effective in attracting new customers and retaining existing ones. In conclusion, effective digital communication and marketing strategies centered on customer value and experience are key to Tedo Cof-fee Shop’s success in a dynamic market. The study recommends continued innovation in digital content and product offerings to maintain competitiveness